Factors Associated with the Behavior of Men who Have Sex with Men in the Prevention of Human Immunodeficiency Virus Transmission - Purwaningsih, Purwaningsih; Adianti, Talia Puspita; Wahyuni, Sylvia Dwi; Arifin, Hidayat (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: The prevalence of HIV/AIDS transmission caused by the behavior of men who have sex with men (MSM) is still a concern. The purpose of this study was to determine the factors associated with MSM behavior in relation to the prevention of HIV transmission. Methods: This study used a cross-sectional design. The total sample was 176 respondents determined using consecutive sampling technique. The variables consist of demographic data, knowledge, attitude, beliefs, the accessibility of the health facilities, health-related skills, peer support, health care provider support and the prevention behavior concerning HIV transmission. The data was obtained using a questionnaire and it was analyzed using Chi-square and ordinal logistic regression. Results: From the sample of 176 MSM, the behavior of the prevention of HIV transmission was 43.75%, which is a moderate level. Through ordinal logistic regression, we found that knowledge [OR:1.171, CI: 0.414-1.929] and peer support [OR: 1.902, CI: 0.721, 3.082] are more likely to prevent HIV transmission. Conclusion: Knowledge and peer support are known to be very important factors concerning the behavior engaged in the prevention of HIV transmission. Increasing the level of knowledge and increasing the youth networks in the form of groups as a form of support can be promoted by nurses, health workers, and the community in order to prevent HIV transmission.